Exuberant as Trend Forecast Method for Kertabumi Klinik Sampah Community Plastic Recycling - Siti Chadijah; Fauziah Latif; Reno Fanthi (Social Economics and Ecology International Journal (SEEIJ), 2020)
Recycling movement is such a never- ending campaign. This movement are grown larger in the society whether in individual or group activities. Any of the groups with the same spirit and vision are blurred in the community to achieve wider impact of recycling plastic. One of the active campaigner is Kertabumi Klinik Sampah which well-known in tinkering any of the recycling technique within the communities around Jakarta. Communities under Kertabumi facilitation are encouraged to turned plastic waste into unique and valuable products. Fostering creativity is the idea of this research aiming to observe the possibility of trend design implementation on the plastic recycle product. Exuberant trend forecasting is used as an approach to designing functional and aesthetical aspect on the product. Moreover, the styling result is offered as a design recommendation for the community to develop their product in the future.